Epidemiology of 1.6 Million pediatric soccer-related injuries presenting to US emergency departments from 1990 to 2003 - Leininger, R. E.; Knox, C. L.; Comstock, R. D. (The American Journal of Sports Medicine, 2007)
As soccer participation in the United States increases, so does the number of children at risk for injury.